The morphology of the upper thorax of Australopithecus Sediba within the context of selected hominoids - Nalla, Shahed (My University, 2014)
The thoracic skeletal morphology of homininae is poorly known and understood. As a result of the representative fossil record of ribs and vertebrae being rare, distorted, fragmentary or unrecognised even when recovered, very little is known about the variability of rib and vertebral morphology when compared to the other cranial and postcranial elements in this lineage. Yet the costal skeleton forms a substantial part of the postcranial skeleton and thus ribs and vertebrae are therefore potentially numerous in the fossil record; but in comparison with other skeletal elements, and for the reasons mentioned above, very little is known about vertebrate and especially hominin rib morphology. The assessment of the structure of the thoracic skeletal elements and its evolutionary and ecological significance, particularly in the Homininae, poses a challenge but is still important as the shape and form of the rib cage has numerous functional and behavioural implications. The present study analysed the ribs of selected primate and non-primate mammalian species by examining fifteen variables, seven indices and eight osteological non-metric features. These observations and measurements were compared to ribs found in the fossil record in order to determine if there are any structural correlates between the extant and the extinct hominin and mammalian species and in order to create a template for the identification of hominin ribs within an abundant and diverse mammalian assemblage. The results suggest that the 1st rib, due to its unique morphology, may be considered most diagnostic in differentiating various taxa. In addition, a template for the morphology of the proximal end of the first rib has been created to be used for both the general as well as the specific identification of fossilised fragments, and to determine thoracic shape. The recently recovered costal elements of the Australopithecus sediba fossils were also examined as one of the most abundant assemblages of the elements in the early hominin record in order to add to our understanding of the morphology, and evolution of this poorly known area of hominin anatomy. The thorax of Australopithecus sediba demonstrates a medio-laterally narrow, ape-like upper thoracic shape, which is different from the broad upper thorax of Homo that has been associated with to the locomotor pattern of endurance walking and running. The lower thorax, however, is less laterally-flared than that of apes, and more closely approximates the morphology found in humans. This indicates a mosaic morphology of the thorax during the human evolutionary linage.
Keywords: Thoracic vertebrae.; Australopithecines.; Fossil hominids.